MODEL COMMUNITY CAPACITY BUILDING ONLINE PENANGGULANGAN BENCANA COVID-19 DALAM ADMINISTRASI PEMBANGUNAN DI PROVINSI BANTEN - Ayuning Budiati; Ipah Ema Jumiati (http://jurnal.untirta.ac.id/index.php/JIPAGS, 2021)
The number of problems that have occurred that accompany the occurrence of the disaster of the spread of covid 19 or corona, which is a pandemic disaster in Indonesia, shows the need for a breakthrough model using the strength of the knots of society that are already owned in the culture of the Indonesian nation and the smallest government structure in Indonesia such as Rukun Tetangga or Rukun Warga, as well as communities that are concerned about disasters or humanity in Indonesia. In development administration science, there is a concept, namely participatory development-autonomous participation, which can be used in disaster management in Indonesia. This study uses a qualitative approach and descriptive analysis method with data collection techniques library research due to ongoing government policies lock down and social distancing as well as physical distancing. This study argues that the use of information technology based on Community Capacity Building Online can tackle disasters in Indonesia based on the aspects of efficiency, effectiveness, transparency and accountability.